Penerapan Manajemen Risiko dalam Usaha Tani Padi di Desa Munjungagung - Putra, Rizky Meisyah; Amirah, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze risk management in rice farming through three main stages: risk identification, risk measurement, and risk management. The study used a quantitative approach by distributing questionnaires to farmers as respondents. One of the main focuses of risk identification was farmers' awareness of the potential for crop failure, which could hamper productivity. The data obtained was analyzed to determine farmers' perceptions of risk sources, the level of impact and probability of risk, and the risk management strategies implemented. The results showed that farmers were aware of various major risks in the rice cultivation process, with the risk of extreme weather and attacks by plant pests as the dominant factors. At the risk measurement stage, farmers assessed that the impact of the risk of crop failure was high and could occur repeatedly within one to two planting seasons. Meanwhile, in risk management, farmers tended to rely on preventive strategies such as the use of superior pest-resistant varieties, adjusting planting times, and regular land maintenance. These findings emphasize the importance of strengthening farm risk management to increase the resilience and sustainability of rice production. This research is expected to serve as a reference in developing policies for mentoring and risk mitigation for farmers.